2022
DOI: 10.3390/antibiotics11070923
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding in Translational Antimicrobial Development-Focus on Interspecies Differences

Abstract: Background/Introduction: Plasma protein binding (PPB) continues to be a key aspect of antibiotic development and clinical use. PPB is essential to understand several properties of drug candidates, including antimicrobial activity, drug-drug interaction, drug clearance, volume of distribution, and therapeutic index. Focus areas of the review: In this review, we discuss the basics of PPB, including the main drug binding proteins i.e., Albumin and α-1-acid glycoprotein (AAG). Furthermore, we present the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Notwithstanding interspecies and strain differences, serum AGP of any one species can change rapidly in response to changing physiological status such as animal handling, housing, stress, age, health status, surgical preparation, activity level, and the presence of inflammation, infection, or injury. The specificity of the analytical AGP method may also contribute to differences where older studies used multi‐step electrophoretic immunodiffusion procedures, 8 while more recent studies use highly specific ELISA 2,3,27 . In summary, when comparing AGP values in the serum of animals and humans, and before standard reference values can be established, it is important to understand the procedural methods and health status of the animal prior to measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding interspecies and strain differences, serum AGP of any one species can change rapidly in response to changing physiological status such as animal handling, housing, stress, age, health status, surgical preparation, activity level, and the presence of inflammation, infection, or injury. The specificity of the analytical AGP method may also contribute to differences where older studies used multi‐step electrophoretic immunodiffusion procedures, 8 while more recent studies use highly specific ELISA 2,3,27 . In summary, when comparing AGP values in the serum of animals and humans, and before standard reference values can be established, it is important to understand the procedural methods and health status of the animal prior to measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-1 acid glycoprotein (AGP) is a significant high-affinity/lowcapacity drug binding and acute-phase protein present in animals and humans. 3,5 With respect to changes in AGP in rats and pigs after hemorrhagic shock, we report the following: (1) mean baseline plasma AGP concentration is 83-fold higher in pigs than in rats; (2) surgical procedures alone were associated with a ~10-fold increase in AGP in rats and a contrasting 21% decrease in pigs; and (3) after hemorrhage and resuscitation, AGP levels in rats decreased 26% over 5 h with little change over the next 3 days, while AGP values in pigs decreased ~8% over 60 min and less than 10% decrease over the next 6 h. We will now discuss these findings, and the possible clinical relevance to higher ALM-doses required in pigs to resuscitate following hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic protein binding, which is an important consideration in plasma PK, is less of an issue when considering free-drug activity and total drug measurements in urine, given the renal excretion of unbound drug and the paucity of albumin found in urine in patients with normal renal glomerular function. 39 , 40 Urinary ciprofloxacin PK variability has been modelled in relation to urine output (1 versus 2.5 L/day), healthy young adults versus elderly, and circadian changes in diuresis and absorption. 41 Such variability in urinary PK is not unique to ciprofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite side, an increased binding rate will result in the reduction of free, active drug concentrations, which may lead to the decreased antimicrobial activity of antibacterial agents in the site of infection, which is extravascular typically. It was also shown that the rate of plasma protein binding of antibiotics can affect the extent of their antimicrobial activity [ 129 ].…”
Section: General Considerations On Neonate’s Pharmacokineticsmentioning
confidence: 99%